1979
DOI: 10.1016/s0022-5347(17)56273-4
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Retroperitoneal Fibrosis: A Systemicconnective Tissue Disease?

Abstract: Renal histology of a patient with idiopathic retroperitoneal fibrosis demonstrated a proliferative crescentic glomerulonephritis with intramembranous electron-dense deposits. These findings were interpreted as being consistent with an immune complex glomerulonephritis. Serologic studies revealed a positive antismooth muscle antibody titer of 1:80 and a weakly positive antinuclear antibody titer of 1:40. No distinct systemic disease was identified. While fibrosis of the retroperitoneum can occur in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

1981
1981
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…Retroperitoneal fibrosis (RPF) is a connective tissue disorder whose primary pathological characteristic is periaortic collagen deposition [1].…”
Section: Introductionmentioning
confidence: 99%
“…Retroperitoneal fibrosis (RPF) is a connective tissue disorder whose primary pathological characteristic is periaortic collagen deposition [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, [1][2][3][4][5] is infrequent and must be distinguished from there was no indication of tumours or metastases. A other retroperitoneal processes [6][7][8][9][10][11][12][13]. Administration weak signal from the fibrous tissue was obtained with of steroids is effective, but causes serious side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…12 Idiopathic retroperitoneal fibrosis is probably immunologically mediated, in view of its response to corticosteroid and immunosuppressive therapy and its occasional association with other immune-mediated diseases. [13][14][15] Immunohistochemical studies have shown that the inflammatory infiltrate is composed The New England Journal of Medicine of B lymphocytes, T lymphocytes that are predominantly of the T-helper phenotype, and macrophages, as in this case. The presence of several cytokines and adhesion molecules has also been demonstrated, confirming the active nature of the inflammatory infiltrate and supporting an immune-mediated mechanism.…”
mentioning
confidence: 67%